Penerapan Bahan Ajar Tahfizh Juz Amma Dalam Meningkatkaan Hafalan Al – Qur’an Di SMP IT Al Karomah Petumbukan - M. Farid Wajdi; Khairuddin Lubis; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
This study aims to explore the implementation of the Tahfizh Juz Amma teaching materials at SMP IT Al Karomah Petumbukan, as well as to evaluate the effectiveness and the supporting and inhibiting factors in the Qur’an memorization learning process. This research uses a field research design with a qualitative approach. Data were collected through participatory observation, in-depth interviews, and documentation. The research subjects consisted of tahfizh teachers and students directly involved in the Qur’an memorization program. The findings reveal that the Tahfizh Juz Amma teaching material is systematically and structurally designed, incorporating tajweed guidelines, step-by-step memorization methods, and weekly memorization targets integrated into the school curriculum. The effectiveness of the teaching materials is supported by institutional commitment, parental involvement, student motivation, and the active role of tahfizh teachers. However, challenges remain, such as limited time, varying memorization abilities, lack of supporting facilities, and inconsistency in muraja'ah (review). Nonetheless, the strategies implemented by the school have proven effective in minimizing these obstacles. Therefore, the implementation of this teaching material is considered effective in improving Qur’an memorization among junior high school students.